Particular aspects in the cytogenetics and molecular biology of salivary gland tumours – current review of reports - Ochal-Choińska, Aleksandra J.; Osuch-Wójcikiewicz, Ewa (Contemporary Oncology/Współczesna Onkologia, 2016)
Salivary gland tumours are a group of lesions whose heterogeneity of biological and pathological features is widely reflected in the molecular aspect. This is demonstrated by an increasing number of studies in the field of genetics of these tumours. The aim of this study was to collect the most significant scientific reports on the cytogenetic and molecular data concerning these tumours, which might facilitate the identification of potential biomarkers and therapeutic targets. The analysis covered 71 papers included in the PubMed database. We focused on the most common tumours, such as pleomorphic adenoma, Warthin tumour, mucoepidermoid carcinoma, and others. The aim of this study is to present current knowledge about widely explored genotypic alterations (such as PLAG1 gene in pleomorphic adenoma or MECT1 gene in mucoepidermoid carcinoma), and also about rare markers, like Mena or SOX10 protein, which might also be associated with tumourigenesis and carcinogenesis of these tumours.